2018
DOI: 10.1101/lm.046391.117
|View full text |Cite
|
Sign up to set email alerts
|

α2-Adrenergic receptor activation promotes long-term potentiation at excitatory synapses in the mouse accessory olfactory bulb

Abstract: The formation of mate recognition memory in mice is associated with neural changes at the reciprocal dendrodendritic synapses between glutamatergic mitral cell (MC) projection neurons and GABAergic granule cell (GC) interneurons in the accessory olfactory bulb (AOB). Although noradrenaline (NA) plays a critical role in the formation of the memory, the mechanism by which it exerts this effect remains unclear. Here we used extracellular field potential and whole-cell patchclamp recordings to assess the actions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…There were 19 transcripts in total ( Table 2 ). AKO mice fed HFD have upregulated transcripts associated with negative regulation of apoptosis [ 42 , 43 , 44 ], neuroinflammation [ 45 ], and ER stress [ 42 , 43 ] along with positive regulation of long-term potentiation [ 46 , 47 , 48 ], spatial working memory [ 49 ], synaptic plasticity [ 50 , 51 ], neurogenesis [ 52 , 53 ], and Wnt/β-Catenin signaling [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 19 transcripts in total ( Table 2 ). AKO mice fed HFD have upregulated transcripts associated with negative regulation of apoptosis [ 42 , 43 , 44 ], neuroinflammation [ 45 ], and ER stress [ 42 , 43 ] along with positive regulation of long-term potentiation [ 46 , 47 , 48 ], spatial working memory [ 49 ], synaptic plasticity [ 50 , 51 ], neurogenesis [ 52 , 53 ], and Wnt/β-Catenin signaling [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The BRD1 protein is needed for H3K14 acetylation [ 63 ], which is associated with synaptic plasticity [ 50 ]. The activation of α2-adrenergic receptors has been shown to promote long-term potentiation in the mouse brain [ 46 ]. Mice lacking MDGA1 and GRIK2 have exhibited compromised hippocampal long-term potentiation [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of presynaptic α2-ARs inhibits N-type calcium channels, neurotransmitter release, and PKA activity, which in turn decreases phosphorylation of receptors 61 . Activation of α2-ARs suppresses the production of cAMP-dependent PKA; in turn, this activates protein phosphatase 1, which inhibits synaptic transmission 62 , 63 and reduces presynaptic glutamate release from mitral cells through Gi/o-protein-mediated inhibition of Ca 2+ channels in the mouse olfactory bulb 64 . In the cerebellar cortex, NA reduces glutamate release at CF-PC synapses via a presynaptic α2-AR-PKA signaling pathway in vitro in mouse 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the cerebellar cortex, α2-ARs play critical roles in information processing and motor coordination skills ( Lähdesmäki et al, 2002 ). A previous study demonstrated that activation of α2-ARs suppresses presynaptic glutamate release from mitral cells by a G i/o -protein-mediated inhibition of Ca 2+ channels in the mouse olfactory bulb ( Huang et al, 2018 ). We previously found that NA inhibits complex spike activity via a presynaptic PKA signaling pathway in vitro ( Cui et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%